Analisis Preferensi Jumlah Anak Ideal di Provinsi Sumatera Utara: Analisis Data Skunder SDKI 2017 - Muhammad Ancha Sitorus; Rosmeri Simarmata; Putra Apriadi Siregar (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2020)
Every family wants to have a certain number of children, this is inseparable from the value of children in each different family so sometimes a family wants 3 to 5 children. The ideal number of children owned by a person will frustrate the achievement of the 2 children program launched by the Indonesian government. The ideal number of children according to someone will be influenced by many things such as education, housing and access to information media. This study uses secondary data of 2017 IDHS using a structured questionnaire and asked the WUS. The study population was married women of childbearing age in North Sumatra Province. The sample in this study was 2459 women of childbearing age who were married. The agency in the 2017 IDHS research used a structured questionnaire. Bivariate data analysis uses Chi-square test and for multivariate analysis uses ordinal logistic regression.The results of this study indicate that there is a significant relationship between residence (p value <0.001), level of education (p value <0.001), radio listening access (p value <0.023), access to the internet with the ideal number of children (p value <0.023) with a preference for the ideal number of children. There was no relationship between family planning field visits (p = 0.376) with the ideal number of children of childbearing age.National Population and Family Planning Agency must be more intense in providing education and outreach about the ideal number of children to women of childbearing age in urban areas. North Sumatea Province BKKBN must be more intense in socializing enough 2 children's programs on the internet and radio media so that women of childbearing age have a preference for the ideal number of 2 children.